2015
DOI: 10.1111/ijs.12602
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis Plan for Evaluating Low- vs. Standard-Dose Alteplase in the Enhanced Control of Hypertension and Thrombolysis Stroke Study (Enchanted)

Abstract: BackgroundThe ENhanced Control of Hypertension And Thrombolysis strokE stuDy trial is a 2 × 2 quasi‐factorial active‐comparison, prospective, randomized, open, blinded endpoint clinical trial that is evaluating in thrombolysis‐eligible acute ischemic stroke patients whether: (1) low‐dose (0·6 mg/kg body weight) intravenous alteplase has noninferior efficacy and lower risk of symptomatic intracerebral hemorrhage compared with standard‐dose (0·9 mg/kg body weight) intravenous alteplase; and (2) early intensive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
0
32
2
Order By: Relevance
“…14 Differential patient recruitment resulted in the part of the trial dealing with alteplase dose being completed faster than the part dealing with intensity of blood-pressure control. For the primary analysis, we used an unadjusted logisticregression model to test whether low-dose alteplase was noninferior to the standard dose.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Differential patient recruitment resulted in the part of the trial dealing with alteplase dose being completed faster than the part dealing with intensity of blood-pressure control. For the primary analysis, we used an unadjusted logisticregression model to test whether low-dose alteplase was noninferior to the standard dose.…”
Section: Resultsmentioning
confidence: 99%
“…17 A new assumption-free approach 21 was used to confirm the conclusion. We also performed secondary analyses of the primary outcome with adjustment for minimization and key prognostic covariates 14 , as well as secondary analyses in the per-protocol population according to criteria outlined in the Supplementary Appendix. Multiple imputation was to be used if more than 10% of observations were missing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this study did not prove non-inferiority of low-dose IV tPA and did not show superiority to the standard dose of IV tPA either. 37 Despite these concerns, ENCHANTED performed well. It was one of the trials which showed that statistical hypothesis testing would not match the clinical performances.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the optimal dose of alteplase may vary according to ethnicity and age. Currently, the Enhanced Control of Hypertension and Thrombolysis Stroke Study (ENCHANTED) is assessing the safety/efficacy of two doses of alteplase (0.6, 0.9 mg/kg) in Australia, Brazil, Chile, China, Colombia, Hong Kong, Italy, Korea, Norway, Singapore, Taiwan, Thailand, the United Kingdom, and Vietnam [11]. ENCHANTED will reveal the optimal dose of alteplase according to ethnicity and age.…”
mentioning
confidence: 99%